RINTISAN KAMPUNG WISATA BERBASIS PEMBERDAYAAN POTENSI KEARIFAN LOKAL MASYARAKAT KAKI BUKIT MARAS KECAMATAN RIAUSILIP KABUPATEN BANGKA - Jamilah Cholillah (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2015)
The tourism village pilot based on empowering the local wisdom potential of the community at the foot of Bukit Maras, Riau Silip Sub-District, Bangka Regency aims to identify and explore the potential of local wisdom stored in the community. This local wisdom potential is deemed necessary to be raised so that the village can complement this area as a tourist destination. The empowerment method uses Focus Group Discussions, Participant Observation, In-depth Interviews and mentoring.The results achieved were the identification of problems faced by the community in order to prepare their village as a tourist village. The problems include, among others, the lack of public awareness in participating in making the village a tourist village, the lack of knowledge related to things that must be prepared to realize a tourist village such as information about the history of the village, the potential of small and medium enterprises, signposts (bars) to natural tourist areas, historical sites and village forests. The achievement of all of these depends on the dynamics of the role and function of community institutions in mobilizing the power of social capital.